Exploring Student Perceptions of Faculty Messages: The Moderating Role of Internationalized Status and Gender - Luurs, Geoffrey; Karabas, Ismail; Wood, Brittany (International journal of applied linguistics, 2025)
Email is a tool used often for developing rapport between students and teachers. A professor's email mistakes may affect the attributions students make about the professor's competence and professionalism. This study used an experimental, between‐subjects design to analyze the impact of professors’ typographical mistakes during initial email interactions and the moderating role of instructor demographics in those perceptions. The final sample consisted of 426 participants (64.6% female, 75.8% Caucasian) across eight universities representing five regions of the United States. The results of this study showed an instructor's email mistakes do lead to negative perceptions. Furthermore, it showed a professor's internationalized status moderated student attributions while gender did not. Though email has a low barrier to entry, mistakes are common and easy to make. The findings of this study highlight the importance of careful communication as a practice, especially during the early stages of a course. 本研究探讨了教师电子邮件的质量如何影响学生对教授专业性、能力及后续好感度的评价, 并分析了教师的国际身份与性别在其中的作用。我们采用实验性的被试间设计, 通过模拟初次邮件互动, 分析教授在邮件中出现拼写错误的影响, 以及教师人口统计学特征的调节作用。最终样本涵盖美国五大地区八所大学的426名参与者 (女性占64.6%, 白种人占75.8%) 。结果显示, 教师邮件中的错误会引发负面评价, 且这种效应对美国本土教师 (相较于国际教师) 更为显著, 表明学生可能 基于对教师母语状态的感知对错误进行差异化归因。然而, 教师的性别未导致显著差异。这些发现强调了精准邮件沟通在塑造学生认知 (尤其是初次互动中) 的重要性, 同时揭示了人口统计特征偏见对学生归因过程的影响。本研究结果进一步指出, 在教学实践中需重视细节沟通, 特别是在课程初期阶段。